DOWNLOAD PDF Persepsi Mahasiwa Terhadap Dakwah Ustadz Derry Sulaiman Berbasis Musik - Muhammad Tarjimy; Nurseri Hasna Nasution (Social Science and Contemporary Issues Journal, 2023)
This research is entitled: "Students' Perceptions of Ustadz Dery Sulaiman's Music-Based Da'wah". This research aims to find out how students perceive music-based Ustadz Derry Sulaiman. This research uses qualitative research. The data collection technique in this research uses interview and documentation methods. The theory used is the theory of Robbins and Toha Yahya Umar. The data analysis techniques used in this research are data reduction, data presentation and conclusion drawing. The results of this research show that students' perceptions regarding Ustadz Dery Sulaiman's music-based da'wah are very effective because based on the facts that researchers obtained in the field regarding the da'wah media used by Ustadz Derry Sulaiman, students form an opinion or perception that the choice of media used by Ustadz Derry Sulaiman is very similar. developments of the times so as to help support the success of his preaching. Advice for Ustadz Derry Sulaiman to continue working through music. Preach through music, because nowadays music has become a part of life. There are so many people who love music so much that it can make a difference in someone's life.